Pratiques Paysannes De Production Durable Des Graines De Voandzou [Vigna Subterranea (L.) Verdc.] Pour La Sécurité Alimentaire Dans Le Cameroun Septentrional - Madou Chantal; Watching Djakissam; Vatsou Jeremie; Ardjoune Fatime; Ndjouenkeu Robert; Goudoum Augustin; Ngassoum Martin Benoit; Ngamo Tinkeu Simon Leonard (European Scientific Journal, ESJ, 2018)
Bambara groundnut is a leguminous plant with high nutritive value of Sub Saharan Africa. In spite of its high potential in alimentation, the Bambara groundnut is less popularized. This crop grows on acid, dry and less fertile soils and may therefore be a resilient crop in the context of climatic variability. The present work aims to identify of all the morphotypes of this culture and the usual tools of conservation of its seeds during the storage process. Investigations carried out during 3 agricultural campaigns showed that women more than 40 years old represents more than 98% of producers of Bambara groundnuts in northern Cameroon. The production concerns 54 morphotypes use as food or as medicinal plants. During storage of grains of this legumes, the major pest is the bruchid Callosobruchus maculatus Fab. (Coleoptera : Chrysomelidae). Under traditional production way, the limitation of the postharvest losses due to this pest is done either by the use of 21 local plants as botanical insecticide or by the use of 25 industrial chemical pesticides.